What Does it Mean to Speak of –––? Rudolf Bultmann, Biography, and J. M. Coetzee's Life & Times of Michael K (1983). (14th December 2017) - Broggi, Alicia
Abstract: From fresh archival evidence we know that J. M. Coetzee was reading works by Rudolf Bultmann, a German New Testament scholar and theologian, while writing Life & Times of Michael K . In these texts Bultmann had developed a conception of the 'meaning' of the Gospel of John, in particular, as inseparable from the reading experience it stages. Notably, he claimed that the Gospel aims to stage a dialectical reading experience: it encourages reliance on mythological language and formal features (thesis), which it then undermines (antithesis), in order to invite potential encounters with the divine, as that which exceeds even the best mythological description (synthesis). Drawing on Coetzee's archived notes, I show how Michael K diffusely reorients this dialectical strategy. Instead of deploying mythological language to invite encounters with the divine, Coetzee relies upon, but also undermines, biographical conventions to cultivate conditions that might expand readers' awareness of the limitations of this narrative before the life it purportedly represents. By tracing a religious register, my reading also foregrounds episodes in which characters undergo encounters that exercise a claim over them, which they cannot quite articulate. Indeed, by attending to Coetzee's readings of Bultmann, I show how this fiction depicts the very phenomenon it stages. For there is good reason to believe that Michael K was specifically crafted with a view toward cultivating attentiveness to ways in which life persistently exceeds representational specificity. Moreover, this was a particularly politically freighted endeavour for an author grappling with life under the apartheid narrative.